2011
DOI: 10.1371/journal.pone.0017977
|View full text |Cite
|
Sign up to set email alerts
|

Association between Non-Suicidal Self-Injuries and Suicide Attempts in Chinese Adolescents and College Students: A Cross-Section Study

Abstract: PurposeThis study examined the association between non-suicidal self-injury (NSSI) and suicide attempts among Chinese adolescents and college students.MethodsA total sample of 2013 Chinese students were randomly selected from five schools in Wuhan, China, including 1101 boys and 912 girls with the age ranging between 10 and 24 years. NSSI, suicidal ideation, suicide attempts and depressive symptoms were measured by self-rated questionnaires. Self-reported suicide attempts were regressed on suicidal ideation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
63
4
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 40 publications
(44 reference statements)
12
63
4
4
Order By: Relevance
“…This observation is consistent with the conclusion of a previous study on Chinese college students [16], and also in high concordance with many reports internationally [17][18][19]. As for the effect of region, there was no significant rural-urban difference for suicidal ideation, but the risk of suicide attempt was significantly higher among students coming from urban areas than those from rural China.…”
Section: Discussionsupporting
confidence: 92%
“…This observation is consistent with the conclusion of a previous study on Chinese college students [16], and also in high concordance with many reports internationally [17][18][19]. As for the effect of region, there was no significant rural-urban difference for suicidal ideation, but the risk of suicide attempt was significantly higher among students coming from urban areas than those from rural China.…”
Section: Discussionsupporting
confidence: 92%
“…Of these studies, 11 studies [16][17][18][19][20][23][24][25][26][27][28] were from PubMed and Embase, while the other 32 studies [21,22,58] published in Chinese were from Wanfang Data, Chongqing VIP and Chinese National Knowledge Infrastructure (CNKI). Among these studies, we removed 63 duplicate studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…These findings suggest that certain factors may act as risk factors for both suicidal and nonsuicidal thoughts and behaviors. This is especially important given the high overlap between these thoughts and behaviors (e.g., Lloyd-Richardson et al, 2007; Tang et al, 2011; Brunner et al, 2007; MacLaren & Best, 2010). Future research disentangling whether this overlap occurs simply because NSSI is predictive of future suicidal behaviors (e.g., does hopelessness predict suicidal thoughts and behaviors when controlling for a history of NSSI?)…”
Section: Discussionmentioning
confidence: 99%
“…This is an especially important risk factor to examine in conjunction with other factors to help discern the unique importance of a given factor above and beyond a history of these behaviors. Moreover, a large body of research has demonstrated that NSSI and suicidal thoughts and behaviors are highly comorbid (e.g., Lloyd-Richardson, Perrine, Dierker, & Kelley, 2007; Tang et al, 2011; Brunner et al, 2007; MacLaren & Best, 2010). Extending upon research examining NSSI as a risk factor for future suicidal behaviors, researchers have also examined whether these thoughts and behaviors are predictive of future NSSI.…”
Section: Introductionmentioning
confidence: 99%